Exosome-Mediated Immunomodulation in Hair Regeneration: From Bench to Bedside - Xinyu, Wei; Osman, Muhamed T. (Trends in Immunotherapy, 2025)
Hair loss still frustrates patients and doctors alike because available treatments yield only modest results; accordingly, researchers are pursuing fresh approaches that target the disorder at its biological roots. The study reported here examined how exosome-based immune tuning affects hair regrowth in mouse models and in ex vivo human follicle cultures. When delivered to skin in the telogen phase, exosomes from adipose stem cells (ADSC-Exo) and from dermal papilla cells (DP-Exo) rewired the local follicular immune environment, and regulatory T cells rose from 2.8 ± 0.5% to 9.1 ± 0.7%, M2 macrophages climbed from 12.4 ± 1.3% to 35.2 ± 2.8%, while potentially harmful CD8 T cells dropped from 28.6 ± 2.4% to 10.2 ± 1.1%. Cytokine profiling revealed a marked decrease in pro-inflammatory signals; hence, TNF-α decreased by 68% and IL-6 by 57%, while simultaneously showing a robust increase in immunoregulatory factors, with IL-10 rising 183% and TGF-β by 156%. The observed changes in immune cell activity appear to have emerged first and closely matched the improved indicators of hair regrowth; in particular, the fraction of regulatory T cells correlated very strongly with hair shaft length (r = 0.84, p < 0.001). Our data indicate that immune reprogramming acts as a central process in exosome-driven hair regrowth, thereby underlining the design of focused immunotherapies for different types of alopecia; however, additional clinical studies are still required.